Regional and subregional analyses of macroeconomic policy strategies for growth and equality in Southern Africa - Dukhabandhu Sahoo; Diptimayee Mishra; Auro Kumar Sahoo; Phendulwa Zikhona Makunga; Jayanti Behera (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
We investigate the relevance of beta (Ø, absolute and conditional) and sigma (σ) convergence in the economies of the Common Monetary Area of Southern Africa and in the provinces of the Republic of South Africa using panel data, allowing an understanding of growth and inequality in the region. The region has experienced Ø- and σ-convergence; however, growth rates of per capita gross domestic product are low at aggregate and sectoral levels. At sectoral level, the performance of the tertiary sector is better than that of the primary and secondary sectors. The relatively poor performance of the primary and secondary sectors needs policy attention. For the provinces of South Africa, capital expenditure on key sectors such as education and health can enhance growth rate, whereas the overall revenue expenditure retards growth. Therefore, provinces' capital budgets need to be managed well within the limitation of revenue expenditure to avoid fiscal imbalances.
Keywords: C23; D63; E13; O47; R11; 330; convergence; growth; inequality; panel data; Southern African region